A critical review of studies of South African youth resilience, 1990 - 2008 - Linda Theron; Adam Theron (South African Journal of Science, 2010)
Given the growing emphasis in research and service provision on strengths rather than deficits, the focus on youth support in the South African Children's Act of 2005 and the lack of educational, therapeutic and other resources for most South Africans, insight into, and transdisciplinary commitment to, resilience is crucial. Resilience, or the phenomenon of 'bouncing back' from adversity, is common to societies that grapple with threatened well-being. Increasingly, international resilience studies have suggested that the capacity to rebound is nurtured by multiple resources that protect against risk and that these resources are rooted in culture. In this paper, we critically reviewed 23 articles that focus on South African youth resilience, published in academic journals between 1990 and 2008. By broadly comparing South African findings to those of international studies, we argued for continued research into the phenomenon of resilience and for a keener focus on the cultural and contextual roots of resilience that are endemic to South Africa. Although international resilience research has begun to match the antecedents of resilience to specific contexts and/or cultures, South African research hardly does so. Only when this gap in youth resilience research is addressed, will psychologists, service providers, teachers and communities be suitably equipped to enable South African youth towards sustained resilience.